Delayed fluorescence, steady state fluorescence, photosystem II quantum yield as endpoints for toxicity evaluation of Cu2+ and Ag+ - Strauch, Sebastian; Richter, Peter; Haag, Ferdinand; Krüger, Marcus; Krüger, Julia; Azizullah, Azizullah; Breiter, Roman; Lebert, Michael (Environmental and Experimental Botany, 2016)
The effect of copper and silver ions on photosynthetic parameters of the flagellate Euglena gracilis was determined. The photosystem II quantum yield (Y) and steady state fluorescence (F) were measured with a PAM-fluorometer, while delayed fluorescence (DF) was determined by means of a sensitive single-photon camera attached to an image analysis device, which counted the relative number of photons released from the algae in darkness after previous light-stimulation. We found that after 3 h of incubation photosynthesis was affected only in the presence of relatively high concentrations of the used noble metals. The obtained EC values for Cu were 505.8 mg L (Y ), 286.5 mg L (DF), and 491.0 mg L (F). The EC values for silver ions were 51.9 mg L (Y ), 51.8 mg L (DF) (values for F not determinable). Photosynthesis is far less sensitive against toxic noble metals compared to motility parameters as reported in earlier studies, in part because the organelles of photosynthesis, the chloroplasts, are well protected from external substances within the cell, while flagella, reaching into the surrounding of the cell, are more easily influenced. As chloroplasts are easily accessible by means of non-invasive methods e.g. PAM- fluorometry, they are probably interesting model systems in order to detect effects of substances deep inside the cell. Influence on the chloroplasts is a measure that a germicide entered the cells, diffused through the cytoplasm and the membranous systems and reached compartmentalized enzyme complexes.
Keywords: Delayed fluorescence; Ecotoxicology; Euglena gracilis; PAM-fluorometry; Photosynthetic yield; Steady state fluorescence